Telaah Faktor-Faktor Anteseden Job Engagement Karyawan PT Z - Mahardika, Yova Era; Setiawan, Rony (Eastasouth Institute, 2024)
Job engagement is one aspect of employment that is crucial to pay attention, to maintain, and to increase its intensity of every employee who works in a company, considering the many positive impacts it can have. Through this research, job engagement will be studied as a result of intrinsic and extrinsic work motivation, work flexibility, and work-life balance. A total of 88 employees who work at PT Z, an e-commerce company in Indonesia, were surveyed regarding their perceptions regarding their work attitudes related to their experience at the company. Using multiple linear regression analysis, it has been proven that job engagement is influenced by intrinsic work motivation, work-life balance, and work flexibility. These results imply that companies need to implement human resource programs and policies that can maintain and improve employees' intrinsic work motivation, the ability and quality of employees in balancing their career and personal life, as well as designing more flexible work in line with current developments and the dynamics of employee needs.